2016
DOI: 10.1101/091314
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacterial genome reduction as a result of short read sequence assembly

Abstract: 7High-throughput comparative genomics has changed our view of bacterial 8 evolution and relatedness. Many genomic comparisons, especially those 9 regarding the accessory genome that is variably conserved across strains in a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Genome assembly methods using short reads are not well suited for genomes with high frequencies of repeated elements [ 76 ]. Because repeat sequences comprise ~40–50 % of the O. tsutsugamushi genome [ 10, 11 ], our genome assemblies were small and highly fragmented, most likely due to repeat collapse [ 17 ]. To demonstrate the effect of un-resolvable repeats on the quality of the genome assembly, we simulated Illumina reads from the completed Boryong genome and assembled them with the same pipeline that was used for real sequence data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genome assembly methods using short reads are not well suited for genomes with high frequencies of repeated elements [ 76 ]. Because repeat sequences comprise ~40–50 % of the O. tsutsugamushi genome [ 10, 11 ], our genome assemblies were small and highly fragmented, most likely due to repeat collapse [ 17 ]. To demonstrate the effect of un-resolvable repeats on the quality of the genome assembly, we simulated Illumina reads from the completed Boryong genome and assembled them with the same pipeline that was used for real sequence data.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction of the O. tsutsugamushi genome assembled with short-read sequencing demonstrates the limitations of this approach and suggests that long-read sequencing approaches would be more appropriate in characterizing the complete genome from this highly repetitive species. We have previously demonstrated that this genome reduction can result in the appearance of missing coding regions [ 17 ], which can complicate comparative pan-genomic analyses. For phylogenetics, the high level of homoplasy complicates inferring all relationships, and demonstrates the importance of quantifying the extent and location of homoplasy before making conclusions on evolutionary relationships.…”
Section: Discussionmentioning
confidence: 99%
“…The amplicons that were used for in silico ribotyping were identified from only three complete ST1 genomes; draft genomes are not useful for the identification of predicted amplicons due to the potential collapse of repeat regions (e.g. 16S rRNA genes) [122]. As additional complete genomes are generated from diverse ribotypes, this method can be modified to associate ribotype information with whole genome sequence and MLST data, which is useful for bridging between different methodologies.…”
Section: Discussionmentioning
confidence: 99%
“…The amplicons that were used for in silico ribotyping were identified from only three complete ST1 genomes; draft genomes are not useful for the identification of predicted amplicons due to the potential collapse of repeat regions (e.g. 16S rRNA genes) (112). As additional complete genomes are generated from diverse ribotypes, this method can be modified to associate ribotype information with whole genome sequence and MLST data, which is useful for bridging between different methodologies.…”
Section: Difficile Isolates Have Been Differentiated Using a Variementioning
confidence: 99%